2023
DOI: 10.1101/2023.07.20.23292968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood epigenome-wide association studies of suicide attempt in adults with bipolar disorder

Abstract: Suicide attempt (SA) risk is elevated in individuals with bipolar disorder (BD), and DNA methylation patterns may serve as possible biomarkers of SA. We conducted epigenome-wide association studies (EWAS) of blood DNA methylation associated with BD and SA. DNA methylation was measured at > 700,000 positions in a discovery cohort of n = 84 adults with BD with a history of SA (BD/SA), n = 79 adults with BD without history of SA (BD/non-SA), and n = 76 non-psychiatric controls (CON). EWAS revealed six differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Other studies have identified immune abnormalities associated with suicidal behavior, including altered inflammatory markers and links to autoimmune disorders [3941]. Our work is also consistent with a recent epigenetic study focused on suicide attempt in BD that found altered DNA methylation in immune-related genes [9]. It is difficult to separate whether these DNA methylation changes are a causal factor of suicide or a consequence of the suicide attempt.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Other studies have identified immune abnormalities associated with suicidal behavior, including altered inflammatory markers and links to autoimmune disorders [3941]. Our work is also consistent with a recent epigenetic study focused on suicide attempt in BD that found altered DNA methylation in immune-related genes [9]. It is difficult to separate whether these DNA methylation changes are a causal factor of suicide or a consequence of the suicide attempt.…”
Section: Discussionsupporting
confidence: 86%
“…The Iowa Neuroscience Institute’s Bipolar Disorder Research Program of Excellence (BD-RPOE) recruited participants, after University of Iowa Institutional Review Board approval, for this study as previously described [9, 11, 20–28]. Written informed consent was provided by all participants and most also provided a blood sample for epi/genetic analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation